Is it Pemphigus Vulgaris or toxic epidermal necrolysis? A dilemmatic condition to confirm diagnosis - Sari, E Fitriana; Setyowati, Titiek (Padjadjaran Journal of Dentistry, 2008)
Pemphigus Vulgaris and Toxic Epidermal Necrolysis both are life threatening diseases. Pemphigus Vulgaris is a mucocutaneous autoimmune disease while Toxic Epidermal Necrolysis is cutaneous drug hypersensitive reaction. It supposes to be easy to distinguish one another, but confusion happens when the clinical appearance is atypical. We report a case which becomes dilemmatic because of some clinical and histological features can be a manifestation from pemphigus vulgaris or toxic epidermal necrolysis. The patient was under supervision by both Oral Medicine Department and Dermatology and Venereal Department. The ulcerative, erosive and sloughing lesion in oral mucosa has been treated successfully by administrating Prednisone 60 mg/ day for almost two months. Epidermal sloughing of more than 10% of total body surface area due to epidermolysis was treated with Methylprednisolone within two months and the epidermolysis is resolved.